Quantification of agility and postural stability in male basketball athletes - Spiteri, T.; Fransen, J.; Scanlan, A. T.; Dalbo, V. J.; Hart, N. H. (Journal of Australian Strength and Conditioning, 2017)
Agility has been identified as an important physiological attribute for basketball performance. Superior agility performance requires basketball athletes to possess tactical attributes used when evading and pursuing opponents, as well as physical attributes to maintain sufficient postural control during dynamic movement. Sensory impairment, diminished joint range of motion, or alterations in neural processing can affect control of body orientation and thus impair postural stability. Impaired postural stability may negatively affect performance and increase injury susceptibility in athletes. Therefore, this study aims to determine differences in agility performance and dynamic posturography (equilibrium and composite scores) through the Sensory Organisation Test (SOT) in male, state-level basketball athletes.